Unreinforced brick masonry wall collapse investigation under moderate wind loads - Aviram, A.; Badillo, J.W.; Prieto, J.A.; Jarammillo, J. D. (Revista Ingeniería de Construcción, 2019)
Several methodologies used for the collapse assessment of an unreinforced brick masonry wall subject to out-of-plane bending due to moderate wind loads in Medellin, Colombia are presented. Models include a rigid cantilever model of masonry elements, deformable cantilever and frame models of intermediate concrete columns and beams with and without masonry contribution to the wind resistance, and a finite element model with all concrete frame elements, masonry units and panel openings modeled explicitly. Wind demands are estimated using spatial interpolation of actual wind velocity measurements near the site. Results are presented in terms of peak deflections at the wall top, as well as peak force and stress demand-to-capacity ratios on concrete frames and masonry elements, respectively. Wind pressure distribution, P-Delta effects, interaction and relative contribution to the out-of-plane bending resistance of concrete framing and masonry elements with either one- or two-way action are shown to be the main parameters affecting results, in addition to model selection. Despite significant differences between models, recommended parameters and assumptions lead in all cases to the correct determination of the wall's imminent collapse under the estimated wind demands